Pengaruh Penerapan Standar Akuntansi Pemerintahan, Kompetensi Sumber Daya Manusia, dan Pengalaman Kerja terhadap Kualitas Laporan Keuangan Pemerintah Daerah (Studi Empiris Organisasi Perangkat Daerah di Kabupaten Sleman) - Barbara Gunawan; Grita Nilakandi (Review of Applied Accounting Research (RAAR), 2026)
This study aims to examine the effect of the implementation of Government Accounting Standards, human resource competence, and work experience on the quality of local government financial reports. The subjects of this study are officials of local government organizations who serve as heads of finance sub-divisions, treasurers, and finance staff in Sleman Regency. The sampling technique used in this study is purposive sampling. This research employs a quantitative approach using primary data collected through questionaries distributed directly to respondents. Based on the questionaires distribution, a total of 126 respondents were obtained as the research sample. Hypothesis testing was conducted using multiple linear regression analysis through SPSS v.29. The results of this study indicate that the implementation of Government Accounting Standards, human resource competence, and work experience each have a positive and significant effect on the quality of local government financial reports. Keywords: Implementation of Government Accounting Standards, Human Resource Competence, Work Experience, Quality of Financial Statements